GIS Land Suitability to Increasing Agricultural Production for the Agriculture Supply Chain: A Systematic Literature Review - Seftin Fitri Ana Wati; Anindo Saka Fitri Fitri; Dhian Satria Yuda Kartika; Anita Wulansari; Eristya Maya Safitri; Agussalim (IJCONSIST JOURNALS, 2022)
Agricultural development is essential for the community's survival because it is a major source of food. Food production is a critical component of food security. Food security must be improved to meet market demand, and one of the fundamental goals of agricultural growth is to provide sufficient quantities of food. Increasing demand for natural resources, as well as environmental issues, are putting pressure on the current agricultural supply chain, which includes agricultural land suitability. Land evaluation is a process of analyzing land resources for specific uses using an established technique or method, and it is required to incorporate land appropriateness. According to the criteria, the findings of land suitability will give information and/or land use guidance. The land's appropriateness might be evaluated in its existing state (actual land suitability) or after changes have been made (potential land suitability). To address these issues, the agricultural sector must transition from traditional agriculture to smart agriculture. One of the technologies and system modeling that drives the current technique to smart agriculture with an integrated approach to evaluate the sustainability of agricultural land suitability is the geographic information system (GIS). The Systematic Literature Review (SLR) from prior investigations is presented in this publication. The articles are divided into two groups based on their approaches: agricultural land appropriateness for rice plants and the application of geographic information systems (GIS), comprising agricultural land suitability, site selection, and effect evaluation. The goal of this research is to determine what criteria are significant in increasing the quality of GIS applications in agriculture. This outcome is expected to assist stakeholders in formulating policies based on the performance of GIS data management in enhancing agricultural productivity and promoting agriculture supply chain management.